KOLABORASI PEMERINTAH KOTA PEKANBARU DALAM PENCEGAHAN DAN PENANGGULANGAN KEKERASAN TERHADAP ANAK TAHUN 2020-2023 - Insani, Syahrina; Pane, Rico Purnawandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Regional Government, Community and Parents have an obligation to protect children based on Pekanbaru Mayor Regulation Number 36 of 2016. Children are the next generation of the nation and state that we should protect, but the situation of children in Indonesia is still and continues to worsen due to violence. Violence against children is any action carried out intentionally or unintentionally that can damage a child, acts of violence include actions, words, attitudes and various structures that occur between two different parties. Theoretically, violence against children is an event of physical, mental or sexual harm which is generally carried out by people who are responsible for the welfare of children. This research aims to describe Pekanbaru City Government Collaboration in Preventing and Overcoming Violence against Children in 2020-2023. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out by means of interviews and documentation. The results of this research indicate that Pekanbaru City government collaboration has not been running optimally, seen from Ansell & Gash's collaborative process theory, namely Face to Face Dialogue, meetings have never been held to discuss preventing and overcoming child violence, Building Trust (Trust Building) yet. maximum because there is no MoU or Decree indicating cooperation. Commitment to the process has not been maximized because the rate of child violence in Pekanbaru City is still high. Sharing understanding has not been optimal because the outreach has not been carried out on a scale. and not optimal, the interim results (Intermediate Outcome) are that the collaborative process has not run optimally so that child violence in Pekanbaru City has increased from 2020-2023. Keywords: Collaboration, Prevention, Mitigation, Child Violence